Optimal liquid culture conditions and bioactivity of Pycnoporus sanguineus - Janice S. Aguilar, Rich Milton R. Dulay, Sofronio P. Kalaw, Renato G. Reyes (Journal of Applied Pharmaceutical Science, 2023)
Pycnoporus sanguineus is a species of mushroom in the Philippines with promising nutritional and pharmacological potentials. In this study, the optimum nutritional and physical growth preferences of P. sanguineus in submerged conditions were established and the biological activities of ethanol extract of its mycelia were determined. The highest yield (100.13 mg/30ml) was produced in rice bran broth with a wide range of pH concentration. Biomass production was favored under 28°C, in lighted and agitated conditions with 147.20 mg/30 ml, 168.47 mg/30 ml, and 413.30 mg/30 ml, respectively. The extract inhibited the growth of Staphylococcus aureus while no antibacterial activity was observed in Escherichia coli. It was found toxic to brine shrimp with an LC50 value of 190.55 μg/ml. Exposure of zebrafish embryos to the extract caused delayed growth resulting in a lower hatching rate. Growth retardation was the most noticeable teratogenic effect of the extract after 48 hours and high mortality rates were observed in high extract concentrations. This study suggests that the optimum biomass yield of P. sanguineus can be achieved when incubated under the most favorable conditions. Mycelia of P. sanguineus could be a valuable resource of antibacterial and cytotoxic compounds.
Keywords: Submerged cultivation, Pycnoporus sanguineus, mycelial biomass, biological activity